An improved kit formulation for one‐pot synthesis of [99mTc]Tc‐HYNIC‐E[c(RGDfK)]2 for routine clinical use in cancer imaging. (18th August 2019) - Chakraborty, Sudipta; Das, Soumen; Chakravarty, Rubel; Sarma, Haladhar Dev; Vatsa, Rakhee; Shukla, Jaya; Mittal, Bhagwant Rai; Dash, Ashutosh
Abstract : Radiolabeled Arg‐Gly‐Asp (RGD) peptide derivatives have immense potential for non‐invasive monitoring of malignancies overexpressing integrin αv β3 receptors. Easy availability of suitable radiotracers would augment the utility of this class of molecular imaging agents. Towards this, the present article describes the development of an improved lyophilized kit for the routine clinical formulation of [ 99m Tc]Tc complex of HYNIC‐conjugated dimeric cyclic RGD peptide derivative E‐[c(RGDfK)]2 (E = glutamic acid, f = phenyl alanine, K = lysine) without using Sn 2+ and systematic evaluation of its efficacy. Five batches of the kits were prepared, and [ 99m Tc]Tc‐HYNIC‐E[c(RGDfK)]2 radiotracer was synthesized with high radiochemical purity (98.6 ± 0.5%) and specific activity (124.8 GBq/μmol) using the kits. Biodistribution studies in C57BL/6 mice bearing melanoma tumor exhibited significant accumulation of the radiotracer in tumor (5.32 ± 0.56 %ID/g at 60 min p.i.), and this uptake was also found to be receptor‐specific by blocking studies. Preliminary human clinical investigations carried out in 10 breast cancer patients revealed high radiotracer uptake in the tumor along with good tumor‐to‐background contrast. The developed kit formulation showed an exceptionally high shelf‐life of at least 18 months. These results demonstrated promising attributes of the developed kit formulation and warrant more extensive clinical investigations.